The effect of financial leverage, firm growth and firm size on profitability: a study of construction companies in Malaysia / Juada Arifin - Arifin, Juada (2018)
The main aim of this research is to investigate the effect of financial leverage, firm growth and firm size on profitability which consists of top 10 construction companies that listed in Bursa Malaysia for year 2011 until 2016. The data collected were analysed using the panel data statistical software. Financial leverage, growth and size are the independent variables and profitability in a proxy of return on asset is the dependent variable. The result in this study reveals that financial leverage in term of debt ratio has significantly demonstrated negative relationship with profitability. This result indicates that the firm should minimize their debt in order to have higher profitability. However, the firm growth shows that there is insignificant relationship towards the profitability, while firm size has positive and significant relationship. It means that the bigger the firm size, it will enhance the profitability and offer higher market growth and business expansion opportunities.